Dishonesty. (March 2019) - ,
This article provides an exposition and assessment of the UK Supreme Court judgment in the case of Ivey v Genting Casinos (UK) Ltd. It identifies the Supreme Court's reconsideration, obiter dictum, of the test of dishonesty in civil and criminal law. This term is used in particular in offences such as those set out in the Theft Act 1968. Prior to the Supreme Court's intervention, the leading case was R v Ghosh [1982] EWCA Crim 2. However, the Ghosh test in that case has been the subject of significant criticism in the academy and elsewhere, and some such critiques are discussed in the Supreme Court judgment. This article, which considers these developments, was first delivered as the Bristol Alumni Association Lecture on 23 February 2018.